New sequence type of an Enterobacter cloacae complex strain with the potential to become a high-risk clone - Knecht, Camila Ayelén (2022)
Objectives: Enterobacter cloacae complex (ECC) has lately awakened interest due to its increasing resistance to carbapenems codified by several genes all over the globe. Even though there are some sequence types (ST) which represent high-risk clones, there is substantial clonal diversity in the ECC. This work aimed to perform whole-genome sequencing (WGS), genomic analysis and phylogenetic studies of a KPC-producing multidrug-resistant (MDR) ECC isolate from Argentina.Methods: We analysed the genome of an MDR KPC-producing ECC strain isolated from a urine sample from a patient in a hospital in Argentina. The WGS was done by Illumina MiSeq-I. The genome was assembled with SPAdes 3.9.0, and annotated with PROKKA, RAST, and Blast. Plasmids were identified with PlasmidFinder. Antibiotic resistance genes were detected using RESfinder, CARD, and Blastn. STs were identified with pubMLST.Results: The strain was identified as Enterobacter hormaechei which is an important emerging human pathogen. No ST could be assigned; 6 out of 7 alleles of multilocus sequence typing (MLST) were the same as for E. hormaechei ST66, which is a high-risk clone. We found multiple acquired antibiotic resistance genes including blaKPC-2 in an IncM1 plasmid, and a secretion system VI, which can favour the prevalence of ECC strains while competing with other bacteria.Conclusions: Due to its MLST profile being so close to E. hormaechei ST66, the acquisition of multiple resistance genes, and the presence of the secretion systems, the potential of this strain for becoming a new high-risk clone cannot be discarded.